STUDY OF HYBRID SYSTEM BETWEEN PLTD AND PLTS ON LEMUKUTAN ISLAND, BENGKAYANG REGENCY - Nabila, Syafa; Abidin, Zainal; Arsyad, Iqbal (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2024)
Lemukutan Island is an island administratively located in Bengkayang Regency, West Kalimantan province. Currently, electrical energy on Lemukutan Island is supplied by 1 unit of Diesel Power Plant (PLTD) which has an installed capacity of 140 kW, but PLTD only operates 14 hours/day, from 16.00 to 06.00 WIB. One of the efforts to be able to provide 24-hour electricity services on Lemukutan Island can be done by operating PLTD for 24 hours and alternative efforts by utilizing hybrid Solar Power Plants (PLTS). In a hybrid system between PLTD and PLTS, researchers calculate the capacity of solar panels, calculate the number of batteries, calculate the number of solar charge contoller, and calculate the capacity of the inverter to be used. The economic analysis used only calculates the initial investment cost and OM costs. Based on the calculation of solar panels used as many as 1473 units with a capacity of 550 Wp, the total watt-peak power is 810 kWp, batteries with a total energy of 2418.9 kWh, Solar Charge Controller using 207 units and 7 inverter units. In the calculation of the total initial investment costs incurred amounted to Rp.10,122,917,594 and investment cost of Rp. 12,497,429/kWp if the installation cost is 0.6%. OM costs amounted to Rp.101,229,175 while the operational and maintenance costs that must be incurred in accordance with the age of the PLTS project that is run following the life of solar panels for 25 years amounted to Rp. 1,760,485,107.